Biofuels from Food Waste : Applications of Saccharification using Fungal Solid State Fermentation - Trzcinski, Antoine Prandota (Boca Raton, FL : CRC Press, 2017)
"According to the UN's Food & Agricultural Organization (FAO), one third of food produced globally for human consumption (nearly 1.3 billion tons) is lost annually. Food waste has often been incinerated with other combustible municipal wastes for possible recovery of heat or other forms of energy, however, incineration is not cost-effective, and can cause air pollution. Due to its organics- and nutrient-rich nature, food waste could be viewed as a useful resource for production of high-value platform chemicals through fermentation. This book examines the bioconversion of food wastes to energy and the recent developments in ethanol, hydrogen, methane, and biodiesel production from food wastes."--Provided by publisher.
chapter 1 Bioconversion of Food Wastes to Energy -- chapter 2 Platform Chemical Production from Food Wastes -- chapter 3 Enzyme Production from Food Wastes -- chapter 4 Enhanced Glucoamylase Production by Aspergillus awamori Using Solid State Fermentation -- chapter 5 Enhancing the Hydrolysis and Methane Production Potential of Mixed Food Wastes by an Effective Enzymatic Pretreatment.
Keywords: Food waste; Biomass energy; Fungi -- Biotechnology; Energy & Fuels; Renewable Energy; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; TECHNOLOGY & ENGINEERING / Environmental / Pollution Control